Aberrant neuronal connectivity and network activity of neurons derived from patients with idiopathic schizophrenia - Johanna Heider; Emilio Pardo González; Sophia-Marie Hartmann; Nirmal Kannaiyan; Sabrina Vogel; Richard Wüst; Andreas J. Fallgatter; Moritz J. Rossner; Udo Kraushaar; Hansjürgen Volkmer (Neurobiology of Disease, 2024)
Schizophrenia (SCZ) is a psychiatric disorder with a strong genetic determinant. A major hypothesis to explain disease aetiology comprises synaptic dysfunction associated with excitatory-inhibitory imbalance of synaptic transmission, ultimately contributing to impaired network oscillation and cognitive deficits associated with the disease. Here, we studied the morphological and functional properties of a highly defined co-culture of GABAergic and glutamatergic neurons derived from induced pluripotent stem cells (iPSC) from patients with idiopathic SCZ. Our results indicate upregulation of synaptic genes and increased excitatory synapse formation on GABAergic neurons in co-cultures. In parallel, we observed decreased lengths of axon initial segments, concordant with data from postmortem brains from patients with SCZ. In line with increased synapse density, patch-clamp analyses revealed markedly increased spontaneous excitatory postsynaptic currents (EPSC) recorded from GABAergic SCZ neurons. Finally, MEA recordings from neuronal networks indicate increased strength of network activity, potentially in response to altered synaptic transmission and E-I balance in the co-cultures. In conclusion, our results suggest selective deregulation of neuronal activity in SCZ samples, providing evidence for altered synapse formation and synaptic transmission as a potential base for aberrant network synchronization.